The Revisitalization of the Querença Market: Exploring the Visitor Experience - Fernandes, Sara; Agapito, Dora; Mendes, Júlio (Journal of Tourism, Sustainability and Well-being, 2015)
Within the paradigm of the experience economy, the literature has recently focused on the importance of creating the conditions to provide individuals with positive, meaningful and memorable consumption experiences. The consumption experience model proposed by Pine and Gilmore, which is based on four dimensions – entertainment, aesthetics, education and escapism – has been operationalized and adapted in several settings. This study presents the results obtained from the analysis of participants’ experiences at the Querença Market, from the perspective of visitors. This initiative is part of a pilot project for territorial intervention – the Querença Project - which was implemented by nine young graduates in the region of Algarve, Portugal. Through a diversified offering of products and cultural and nature-related activities, based on the co-creation process with the local community, it was possible to revitalize the traditional village market, which became extinct 70 years ago. The results of the questionnaires presented to visitors of the market highlighted the multi-sensory nature of the event, which is related to the wide diversity of sensory stimuli associated with food, agricultural products and human interaction. Visitors described an overall positive and memorable experience, emphasizing the dimensions related to “aesthetics” and “entertainment.”